Kejserkult i den romerske husstand - Gradel, Ittai (Religionsvidenskabeligt Tidsskrift, 1990)
A recurrent statement in scholarship on the Roman imperial cult has been that the phenomenon was but a political expression of loyalty towards the emperor, involving little “truly religious” sentiment for the worshippers. According to this argument, the cult was almost exclusively a public phenomenon. Private emperor worship has received surprisingly little attention from scholarship, but even in the unequivocally private sphere of the Roman household (in Italy), the cult of the living emperor seems to have been widespread during early imperial times. Although the difficult nature of the source material for private emperor worship calls for caution, this conclusion forms a basis for rejecting the traditional interpretation of the imperial cult as reductionist and Christianizing.